Intervening fish post‐harvest losses to narrow the gap between demand and supply: A review on magnitude of fish post‐harvest losses in some Sub‐Saharan African countries - Alemu Lema Abelti; Tilahun A. Teka (Aquaculture, Fish and Fisheries, 2024)
Abstract This review was aimed to summarize the extent and causes of fish post‐harvest losses (FPHLs) in Sub‐Saharan African (SSA) countries and suggests the necessary intervention measures to narrow the gap between demand and supply. Globally, an estimate of 10–12 million tons of fish is lost per year. FPHLs in SSA are higher than those in other parts of the world. In SSA, the values of fisheries are estimated at 24 billion USD, 1.26% of the GDP of all the African countries and 6% of agriculture GDP. The vast majority of FPHLs in SSA occur at the production (39%), handling (36%), distribution (13%), processing (7%) and consumption (5%). The major factors that cause FPHLs in SSA were long time spent in hauling of fishing gears, spoilage, size discrimination, species preferences, operational losses, animal predation, poor handling practices, lengthy duration of fishing cycle, failure to use ice, lack of storage facilities, lack of transportation and insect infestation. FPHLs amount one third of total production and financial losses of 2–5 billion USD in SSA countries. Furthermore, volarization of fish waste and converting waste into useful substances is a promising approach to reduce fish waste. It can be recommended that improving fish production, live fish handling, processing, preserving, and marketing in SSA could narrow the gap between fish demand and supply.